2013
DOI: 10.1186/2049-6958-8-25
|View full text |Cite
|
Sign up to set email alerts
|

Hemoptysis in patients of celiac disease with disproportionately severe anemia: tip of the iceberg?

Abstract: Idiopathic Pulmonary Hemosiderosis (IPH) is characterized by the triad of iron deficiency anemia, pulmonary infiltrates and haemoptysis with no recognizable cause. Since the first description of its association with Celiac Disease (CD) by Lane and Hamilton in 1971, only a few isolated cases have been reported in literature. Although it has been considered an uncommon association of two disease entities, recent reports indicate that prevalence of celiac disease is as high as one percent. Further, individually b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 20 publications
(11 reference statements)
1
21
0
Order By: Relevance
“…Among few published cases of Lane Hamilton syndrome, six cases are Indian with male predominance and being diagnosed very late similar to our case [3,4]. Furthermore, suspicion for both components of the syndrome is very low despite higher disease prevalence (1%) of CD in North India [2].…”
supporting
confidence: 71%
“…Among few published cases of Lane Hamilton syndrome, six cases are Indian with male predominance and being diagnosed very late similar to our case [3,4]. Furthermore, suspicion for both components of the syndrome is very low despite higher disease prevalence (1%) of CD in North India [2].…”
supporting
confidence: 71%
“…In the cases reviewed, different clinical situations explained the development of hemorrhagic events, such as coagulopathy due to vitamin K malabsorption [4,15,20,23,32,44,45,47], celiac crisis [8,13], LHS [14,15,17,18,[33][34][35][36][37][38][39][40], portal hypertension [23], or digestive tumors [19,21,25,41].…”
Section: Discussionmentioning
confidence: 99%
“…In 1971, the IPH presence was described in a 23-year-old man with idiopathic steatorrhea (LHS) [63]. The pulmonary symptomatology in LHS starts usually in childhood, and only 25% of all patients have an adult onset [14,35]. Xi-Yuan et al reviewed the literature for IPH and identified 37 patients (12 women, 24 men), out of whom 5 had CD [64].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations